Familial true hermaphrodism in three siblings: clinical, cytogenetic, histological and hormonal studies - Armendares, S; Salamanca, F; Cantú, J M; Del Castillo, V; Nava, S; Dominguez-de-la-Piedra, E; Cortés-Gallegos, V; Gallegos, A; Cervantes, C; Parra, A (Humangenetik, 1975)
Three affected siblings with the hermaphrodism are described. The propositi showed the following characteristics: male phenotype and gender role, hypospadias, bilateral scrotal ovotestes with palpable nodules, and absence of müllerian structures. The X chromatin was positive and the Y chromatin was negative in the 3 affected subjects. Their karyotype in peripheral blood lymphocytes and in gonadal fibroblasts was 46,XX and no Y chromosome fluorescence was observed. Plasma FSH was elevated in the 2 older patients and plasma LH was elevated only in the oldest. Plasma testosterone was low and plasma estradiol high in the 3 siblings; plasma progesterone was elevated in 2, but normal in 1 sibling. Since some of the clinical characteristics of these 3 affected siblings are not the most common features in the majority of sporadic cases of true hermaphrodism, it is suggested that the presence of all of them may be the first clue for the clinical suspicion of the familial type of true hermaphrodism.